2008
DOI: 10.1080/03009740801914850
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography before and after surgery in carpal tunnel syndrome and relationship with clinical and electrophysiological findings. A new outcome predictor?

Abstract: CSA-I is the most sensitive US measurement before surgery. The presurgical value of CSA-I is a predictor of postsurgical normalization of clinical parameters and of its own value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
64
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 21 publications
8
64
2
2
Order By: Relevance
“…This might be explained by the larger amount of soft tissue and structures surrounding the tibial nerve, leading to more diffusely spread pressure. In patients with idiopathic carpal tunnel syndrome and without diabetes, release of the flexor retinaculum results in a decrease of CSA (27)(28)(29). One study showed an increase of CSA and T/W ratio (30).…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the larger amount of soft tissue and structures surrounding the tibial nerve, leading to more diffusely spread pressure. In patients with idiopathic carpal tunnel syndrome and without diabetes, release of the flexor retinaculum results in a decrease of CSA (27)(28)(29). One study showed an increase of CSA and T/W ratio (30).…”
Section: Discussionmentioning
confidence: 99%
“…Our data based on the CSA measurements show additional facts. If there was exclusive constriction only to the axonal flow, the corresponding nerve should be swollen in a pseudoneuroma-like manner mainly proximal to the point of relevant constriction and show distal to that rather "normal" caliber as known from carpal tunnel syndrome [16,17]. This is (astonishingly!)…”
mentioning
confidence: 99%
“…Ergebnisse: Textur-VerĂ€nderungen konnten in 4,6 (76,7 %) ± 1,2 nachgewiesen werden, VerĂ€n-derungen der Ă€ußeren Nervenscheide in 4,1 (68,3 %) ± 1,1 der Segmente. Kaliber-VerĂ€nderun-gen basierend auf die 6 Segmente konnten nachgewiesen werden: eine CSA von 7,45 mmÂČ Â± 2,24 wurde proximal des oberen Faszien-Durchtritts (PUF) gefunden, am oberen Faszien-Durchtritt (UF) eine mittlere CSA von 11,96 mmÂČ Â± 3,61, distal des oberen Faszien-Durchtritts (DUF) eine mittlere CSA von 11,49 mmÂČ Â± 8, 16, proximal des unteren Faszien-Durchtritts (PLF) eine mittlere CSA von 10,84 mmÂČ Â± 4,73, am unteren Faszien-Durchtritt (LF) eine mittlere CSA von 12,12 mmÂČ Â± 5 und distal des unteren Faszien-Durchtritts (DLF) eine mittlere CSA von 7,89 mmÂČ Â± 3,42. Alle verlagerten Nerven zeigten relevanten Knickstellen an der UF, 6 Nerven prĂ€sentierten relevanten Knickstellen an der LF.…”
unclassified
“…Mondelli et al14 reported post-operative changes in CTS patients. They found that ultrasonography was useful for the diagnosis of CTS, providing anatomical images of the median nerve, carpal tunnel, and neighboring structures, as well as for demonstrating improvement following surgical release.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography in CTS is variable and controversial, and some studies have evaluated the median nerve CSA at the carpal tunnel inlet, outlet, and mid-portion 14,16,17,19. The present study only used the maximal CSA 15.…”
Section: Discussionmentioning
confidence: 99%